Reducing delinquency among African American youth in foster care: Does gender make a difference in crossover prevention?. (November 2018) - Williams-Butler, Abigail
Abstract: It is well established that crossover youth (those involved in the child welfare system who go on to be involved in the juvenile justice system) are disproportionately African American youth. However, little is known about the factors which reduce the risk of delinquency among this population. Participants were 534 adolescents who completed the Illinois Department of Children and Family Services Child and Adolescent Needs and Strengths assessment between 2007 and 2012. This study sought to identify the multilevel promotive factors among this population and assess whether these factors later reduced the likelihood of delinquency. It was hypothesized that youth have promotive factors at the individual, contextual, and system level and that each factor differed in importance by gender. Findings indicate that African American youth do have promotive factors across a range of domains. For all youth, age and time in care were important for reducing the risk of delinquency. Counterintuitively, social relationships were associated with an increased risk of delinquency. School achievement, caregiver resources, and time in care were more influential for African American males. Age was more influential for African American females. Implications for practice and policy are discussed. Highlights: African American youth in foster care have promotive factors across a range of domains. Age and time in care were important for reducing the risk of delinquency for all youth. Counterintuitively, social relationships were associated with an increased risk of delinquency for all youth. School achievement, caregiver resources, and time in care were more influential for African American males. Age was more influential for African American females.